Update in the classification and the role of intra‐arterial stenting in the management of carotid body paragangliomas. Issue 5 (16th February 2019) - Prasad, Sampath Chandra; Laus, Melissa; Al‐Ghamdi, Saeed; Vashishth, Ashish; Piazza, Paolo; Sanna, Mario
Abstract: Background: To review the Shamblin classification of carotid body paragangliomas (CBPs) and the role of intra‐arterial stenting in their surgical management. Methods: Retrospective case series of 20 patients with 28 CBPs that were surgically resected at our center. Intra‐arterial stenting was performed in Shamblin II and II classes. Results: The mean follow‐up was 47.8 months. Five (17.9%) tumors were Shamblin class I, 15 (53.6%) were class II, and 8 (28.6%) were class III. Thirteen (68.4%) CBPs were associated with other paragangliomas. The internal carotid artery (ICA) was stented preoperatively in eight (28.6%) cases and occluded in four (14.3%) cases. The tumor extended to the jugular foramen in six cases (21.4%). Intraoperatively, there was an ICA injury in one case of Shamblin II CBP in the present era. Conclusions: The proposed classification enables the clinician to plan the management of the ICA and the right approach. Stenting of the ICA gives a chance for complete tumor removal with arterial preservation.